The research on relationship among chefs & its effect towards their turnover rates / Mohd Azuan Mohd Alias ... [et al.] - Mohd Alias, Mohd Azuan; Abdullah, Rahman; Dolah @ Abdullah, Siti Noraisah; Salleh, Hamdin (2008)
Services represent the majority of today’s economy, not only in developed countries but also developing countries throughout the world. In most countries, the service sector of the economy is very diverse, comprising a wide array of different industries that sell to individual customers and business customers as well as to government agencies and nonprofit organizations (Lovelock and Wright, 2002). Service industries also account for most of the growth in new jobs (Brayner, 1997). In Malaysia, the tourism industry has been identified as the key driver in the growth of the service sector (Economic Planning Unit, Prime Minister’s Department, Malaysia, http;//www.epu.jpm.my). However, the growth of the service industry and the tourism industry in Malaysia as a whole is being embittered by the high turnover rate in the hotel industry, which plays a major role in the service, as well as the tourism industry. This research undertakes a descriptive research methodology in which questionnaires had been distributed among employees in 5 star hotels in Klang Vailey area, which is considered as a lucrative hospitality spot in the country. The findings appear to support the hypotheses that there are significant correlation between Chef Relationship in the kitchen and their turnover rates. Among many things, the most prevalent criteria are the relation among Chef appears to influence greatly the turnover rates among Chef in the kitchen, their income, their post in the kitchen, and their education level seems to have some connection that actually influence their decision to stay in the same organization.